Peranan Bank BPRS PT Puduarta Insani Dalam Meningkatkan UMKM melalui Program Pembiayaan Murabahah - Kholifah Kholifah; Sri Sudiartri (VISA: Journal of Vision and Ideas, 2022)
This study aims to determine how the role of the BPRS bank PT. Puduarta Insani in increasing MSMEs through the murabahah financing program. This study uses a descriptive qualitative method by obtaining data through interview techniques conducted on several bank employees and MSME actors involved in this program as well as secondary data originating from the BPRS website with time series data for five years. The results of this study indicate that Bank BPRS Pt.Puduarta Insani has a role in increasing MSME financing and the number of customers for the last five years, namely from 2016 to 2020. This is shown by the number of customers in 2016 only around 188 people but in 2020 it has reached 240 customers who joined, this shows that the financing with the murabahah system carried out by Bank BPRS Pt. Puduarta has a positive effect on increasing MSMEs. Keywords: Murabaha Financing, MSME